2007
DOI: 10.1097/moh.0b013e3282c8ca50
|View full text |Cite
|
Sign up to set email alerts
|

Should rituximab be used before or after splenectomy in patients with immune thrombocytopenic purpura?

Abstract: Both the response rate and the response duration appear lower following rituximab than following splenectomy. Although the side effects may be fewer, there is insufficient evidence to support the replacement of splenectomy with rituximab as a second-line treatment of chronic immune thrombocytopenic purpura outside a clinical trial. At the present time, the use of immunotherapy before splenectomy can be recommended only in patients at high risk for splenectomy and in those not willing to undergo surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
1
28
1
4
Order By: Relevance
“…A splenectomy may lead to severe postoperative complications, including venous thromboembolism, serious infections, or bleeding [10], and even mortality, all of which are of even greater concern for elderly and frail patients [11,12]. Moreover, older ITP patients may be less likely to respond to splenectomy [8,13,14]. Our finding that rate of splenectomy was higher among patients with higher disease activity are consistent with the guidelines for cITP treatment.…”
Section: Discussionsupporting
confidence: 79%
“…A splenectomy may lead to severe postoperative complications, including venous thromboembolism, serious infections, or bleeding [10], and even mortality, all of which are of even greater concern for elderly and frail patients [11,12]. Moreover, older ITP patients may be less likely to respond to splenectomy [8,13,14]. Our finding that rate of splenectomy was higher among patients with higher disease activity are consistent with the guidelines for cITP treatment.…”
Section: Discussionsupporting
confidence: 79%
“…The persistence of the response is a crucial issue to evaluate the role of rituximab in the treatment of resistant pITP and especially to evaluate if this drug could be a valid alternative to splenectomy. Cooper et al [20] reported that the long-term response rate of splenectomy is consistently higher than that obtained with rituximab. Godeau et al [8], in a prospective multicentric phase II study aimed at evaluating the efficacy and safety of rituximab in chronic ITP patients who were potential candidates for splenectomy, reported that at 2 years, 40% of patients (24/60) had a platelet count ≥30 × 10 9 /l off treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8 Whether it could be an effective and safe splenectomy-avoiding strategy in adults with chronic ITP remains unresolved. 22 To assess rituximab efficacy and safety in nonsplenectomized adults with chronic ITP (duration Ն 6 months), we conducted a prospective, multicenter, open-label, single-arm phase 2 trial using Fleming singlestage design. …”
mentioning
confidence: 99%